Microcavity‐Enhanced Light‐Trapping for Highly Efficient Organic Parallel Tandem Solar Cells. (28th August 2014) - Zuo, Lijian; Chueh, Chu‐Chen; Xu, Yun‐Xiang; Chen, Kung‐Shih; Zang, Yue; Li, Chang‐Zhi; Chen, Hongzheng; Jen, Alex K.‐Y.
<x xml:space="preserve">Abstract</x> A high‐performance parallel tandem solar cell employing ultra‐thin Ag as the intermediate anode is demonstrated, which comprises a semitransparent front sub‐cell and a microcavity assisted back sub‐cell. In addition to the extended optical field as a result of the tandem architecture, the prominent microcavity resonance formed in the back sub‐cell enables such a parallel tandem configuration to possess high light utilization efficiency (the peak EQE value is over 80%) and a high photovoltaic performance of 9.2%. This study establishes an effective architecture that can be generally applicable to all organic materials for improving their performance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>